Functional foods and cardiovascular disease - Moghadisian, Mohammed H.; Eskin, N. A. M. (CRC Press, 2012)
"Drawn from the latest clinical and experimental information, this book covers cover products enriched with phytosterols, n-3 fatty acids, garlic extract naturally occurring antioxidants, folic acid, CLA, as well as fibers and flavonoids. It describes the connection between diets, dietary habits, and cardiovascular diseases. It also explains how functional food ingredients and nutraceuticals can mitigate cardiovascular disorders. The authors examine recent technologies for generating novel food products enriched with cardiovascular protective dietary agents. They include experimental and clinical evidence of various ingredients"--